2012
DOI: 10.1182/blood-2012-03-418681
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of M-DC8+ monocytes from viremic HIV-infected patients in TNFα overproduction in response to microbial products

Abstract: HIV infects activated CD4 ؉ T cells and induces their depletion. Progressive HIV infection leading to AIDS is fueled by chronic immune hyperactivation, mediated by inflammatory cytokines like TNF␣. This has been related to intestinal epithelial damage and microbial LPS translocation into the circulation. Using 11-color flow cytometry, cell sorting, and cell culture, we investigated the numbers and TNF␣ production of fully defined circulating dendritic cell and monocyte populations during HIV-1 infection. In 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
82
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 51 publications
9
82
0
4
Order By: Relevance
“…We classified purified monocytes according to CD14 and CD16 expression and measured the LY6E levels in these subsets to exclude the possibility that the observed elevation in LY6E levels is due to perturbation in monocyte subsets in HIV infection (32,33 ART-naive subjects with low CD4 count compared with those from subjects with high CD4 count, and this elevation appeared to be decreased after suppression of viral replication by ART (Fig. 2G).…”
Section: Correlation Of Elevated Ly6e Expression In Monocytes To Hiv mentioning
confidence: 99%
See 1 more Smart Citation
“…We classified purified monocytes according to CD14 and CD16 expression and measured the LY6E levels in these subsets to exclude the possibility that the observed elevation in LY6E levels is due to perturbation in monocyte subsets in HIV infection (32,33 ART-naive subjects with low CD4 count compared with those from subjects with high CD4 count, and this elevation appeared to be decreased after suppression of viral replication by ART (Fig. 2G).…”
Section: Correlation Of Elevated Ly6e Expression In Monocytes To Hiv mentioning
confidence: 99%
“…7A, 7B), indicating that monocytes from HIV patients are in a heightened activation state perhaps owing to persistent viral replication, exposure to homeostatic cytokines, and to microbial products (33)(34)(35). Furthermore, to directly examine the immunosuppressive role of LY6E in HIV infection, CD14…”
Section: Ly6e Represses the Responsiveness Of Primary Monocytes To Lpmentioning
confidence: 99%
“…Preexposure of monocytes to the TLR7/8 pathway triggered by HIV-1 ssRNA-derived ligands has been considered the causative factor for the increased LPS/TLR4 responsiveness (15). Other studies have focused on the skewed differentiation of monocyte subgroups during HIV-1 infection and observed that proinflammatory CD16 ϩ monocytes and TNF-␣-producing M-DC8 ϩ CD14 ϩ CD16 ϩϩ monocytes were more expanded in chronic HIV-1 infection than in healthy subjects (7,9,17,49). Interestingly, the expansion levels of these cells appear to vary among different reports (7,8,49).…”
Section: Mir-126-5p Enhances Monocyte Responses To Lpsmentioning
confidence: 99%
“…Preexposure of monocytes to Toll-like receptor 7/8 (TLR7/8) ligands derived from HIV-1 single-stranded RNA (ssRNA) (14,15) and upregulated TLR2 expression on monocytes (16) could enhance the inflammatory responsiveness of these cells. In addition, skewed differentiation of monocytes into proinflammatory CD16 ϩ monocytes and tumor necrosis factor alpha (TNF-␣)-producing M-DC8 ϩ CD14 ϩ CD16 ϩϩ monocytes during chronic HIV-1 infection have been observed in the presence of HIV-1 viremia compared to that observed in HIV-1 seronegative subjects (7,9,17). Effective antiretroviral therapy (ART) successfully suppresses HIV-1 replication but fails to normalize monocyte activation/inflammation (3,(18)(19)(20)(21).…”
Section: Abstract Cyld Hiv-1 Inflammatory Responses Mir-126-5p Momentioning
confidence: 99%
See 1 more Smart Citation